Energy saving via Heat Pipe Heat Exchanger in air conditioning applications "experimental study and economic analysis". (March 2021) - Abdelaziz, Gamal B.; Abdelbaky, M.A.; Halim, M.A.; Omara, M.E.; Elkhaldy, I.A.; Abdullah, A.S.; Omara, Z.M.; Essa, F.A.; Ali, Aml; Sharshir, Swellam W.; El-Said, Emad M.S.; Bedair, Ahmed G.; et al.
Abstract: In this work, an experimental study on energy saving for air conditioning application has been conducted. Heat Pipe Heat Exchanger (HPHX) was installed between the fresh air and return air streams to cool the fresh air before entering the air handing unit. Three test sections of wickless HPHX of different pipe diameters were tested. The studied test section inner diameters were 7.9, 10.2 and 16.56 mm. The study was conducted at different fresh air inlet temperatures to check the effect of ambient temperature on fresh air cooling. The mass flow rate ratio between return and fresh air was chosen to be 1, 1.5, 2 and 3. The obtained results indicated that the effectiveness of HPHX, the ratio of actual rate of heat transfer by HPHX to the maximum possible heat transfer rate between the two air streams, increases with the increase of fresh air inlet temperature, the ratio between return and fresh air mass flow rate, and heat pipe diameter. An energy reduction of about 30% was resulted due to inserting a wickless HPHX in the system with inner diameter 10.2 mm, average fresh air inlet temperature 35 °C and equal masses of fresh and return air streams. Economic analysis showed that the energy-saving decreases electrical consumption cost with a payback period of about three years with lifetime about 20 years.